High internal phase Pickering emulsion by ultrasound-modified almond protein isolate particles as a new fat substitute to improve oxidative stability of pork sausages - Yang, Qingrui; Han, Peng; Qi, Wenhui; Shao, Yutong; Zhang, Xu; Wu, Fengyang; Zhang, Zhisheng (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn this study, high-internal-phase Pickering emulsions (HIPPE) were used to produce low-fat meat products. The oxidative stability of HIPPE is a critical factor determining its suitability for this application.MethodsAccordingly, an investigation was conducted to ascertain the impact of substituting 25–100% pig back fat with HIPPE (75% soybean oil, v/v) stabilized with ultrasound-modified almond isolate protein (UAPI) particles on the stability of sausages.ResultsThe 300 W-UAPI sample exhibited the highest surface hydrophobicity value and emulsification activity index (87.65 m2/g), as well as the most optimal foaming stability (90.93%). Compared to the control emulsion, 300 W-UAPI-HIPPE exhibited the smallest average droplet size (30.49 μm), the highest oil loading ratio (82.26%), and improved antioxidant properties. The incorporation of UAPI-HIPPEs in sausages resulted in enhanced textural properties, including hardness, elasticity, chewiness, adhesion, and resilience, as well as increased densification. In addition, cooking loss and thiobarbituric acid-reactive substances content were reduced. Among the samples, those with 100% backfat substitution exhibited the most favorable textural properties and micromorphology, with a 67% reduction in cooking loss and the lowest fat oxidation.DiscussionThese findings indicate that UAPI-HIPPEs may serve as viable alternatives to animal fat in meat products, exhibiting desirable characteristics.